HUBUNGAN PENGETAHUAN IBU DENGAN UPAYA PENCEGAHAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI PUSKESMAS TUNTUNGAN TAHUN 2022 - Maria pujiastuti; Pomarida Simbolon; Sr. Sri Martini; Novrianti Purba (Jurnal Cakrawala Ilmiah, 2023)
Acute respiratory infections (ARI) are a major health problem in children under five years of age (toddlers). Mother's knowledge also affects the incidence of ARI in toddlers. The purpose of this study is to determine the relationship between maternal knowledge and efforts to prevent acute respiratory infections (ARI) in toddlers at the Tuntungan Health Center in 2022. This research method use a cross sectional approach. The sampling technique in this study use a purposive sampling technique with a total of 37 respondents. The instruments used in this study are maternal knowledge instruments and ARI prevention instruments. The results show that the knowledge of the mother is in the good category (73.0%) and the prevention of ARI is good (78.4%). The results of the Chi-square statistical test with p value = 0.001 (p <0.05), meaning that there is a relationship between mother's knowledge and efforts to prevent acute respiratory infections (ARI) in children under five at the Tuntungan Health Center 2022. It is hoped that the leadership and staff of the Tuntungan Health Center carry out health education programs about Acute Respiratory Infections (ARI) for the community, provide and improve counseling through various health information media on social media that has developed recently.